Health-oriented leadership and mental health from supervisor and employee perspectives: a multilevel and multisource approach - Vonderlin, Ruben; Schmidt, Burkhard; Müller, Gerhard; Biermann, Miriam; Kleindienst, Nikolaus; Bohus, Martin; Lyssenko, Lisa (Frontiers in psychology, 2021)
The link between leadership and mental health at the workplace is well established by prior research. However, most of the studies have addressed this relationship from a single-source perspective. The aim of this study was to examine how supervisor and employee ratings of health-oriented leadership correspond to each other and which sources are predictive for employee mental health. We assessed data within 99 teams (headed by 99 supervisors) containing 713 employees in 11 different companies in Southern Germany. Supervisors and their staff completed questionnaires on the supervisors’ health-oriented staff-care dimensions awareness, value of health and health behavior (Health-Oriented Leadership Scale, HoL) and current mental distress (Hospital Anxiety and Depression Scale, HADS). Hierarchical linear models revealed that supervisors’ self-ratings were significantly related to their employees’ ratings (at the team level) only on the health behavior dimension, but not on the health awareness and value of health dimensions. Also, supervisors rated themselves significantly higher on HoL compared to their employees. Employee ratings of HoL significantly predicted their own level of mental distress (direct within-level effect), whereas supervisor ratings of HoL did not predict employees’ mental distress at the team level (direct cross-level effect). Supervisors’ self-ratings of HoL did not influence the relationship between employee ratings of HoL and their mental health on an individual level (cross-level interaction). These results highlight the complex relationship between multisource assessments of HoL and employee mental health, emphasizing the importance of subjective perception for mental health. Future studies should investigate under which conditions supervisor and employee ratings correspond to each other and are predictive for mental health at the workplace.
Gesehen am 09.02.2021